2003
DOI: 10.1046/j.1365-2265.2003.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

The glutamine 27 glutamic acid polymorphism of the β2‐adrenoceptor gene is associated with abdominal obesity and greater risk of impaired glucose tolerance in men but not in women: a population‐based study in Spain

Abstract: Our results suggest that the glutamic acid 27 allele of the beta2-adrenoceptor may be a risk factor in men but not in women for the accumulation of visceral fat and for its association with the development of type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…12 studies were excluded because groups were not divided by BMI [6], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23] and one paper was excluded due to the fact that data correlating ADRB2 with obesity were not available[24]. Thus, 18 studies [4], [6], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40] met our inclusion criteria. Of these, 17 papers involving 9,995 subjects genotyped at rs1042714 (all except Angeli et al [39]) and 10 studies [4], [6], [25], [26], [28], [30], [31], [33], [39], [40] including 7,322 subjects genotyped at rs1042713 were included.…”
Section: Resultsmentioning
confidence: 99%
“…12 studies were excluded because groups were not divided by BMI [6], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23] and one paper was excluded due to the fact that data correlating ADRB2 with obesity were not available[24]. Thus, 18 studies [4], [6], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40] met our inclusion criteria. Of these, 17 papers involving 9,995 subjects genotyped at rs1042714 (all except Angeli et al [39]) and 10 studies [4], [6], [25], [26], [28], [30], [31], [33], [39], [40] including 7,322 subjects genotyped at rs1042713 were included.…”
Section: Resultsmentioning
confidence: 99%
“…22 Obese Spanish men with the Glu27Glu genotype had higher 2 hour post-load glucose concentrations compared with the Gln27Gln genotype. 23 Some studies also have found an association between the Gln allele and higher triglycerides concentrations, 25,26 while other investigators did not find an association between β2-AR and lipid levels. 27-29 …”
Section: Discussionmentioning
confidence: 97%
“…These findings show that the genetic background, especially β 2- and β 3-adrenoceptor polymorphisms, are associated with sympathetic nervous system activation, and are important in the pathogenesis of obesity-related hypertension and insulin resistance. Many investigations regarding the relationships between β -adrenoceptor polymorphisms and obesity have been analysed; however, the results are discordant [30–32]. …”
Section: Introductionmentioning
confidence: 99%